ANALISIS GUGUS FUNGSI OBAT SIRUP BATUK DENGAN FOURIER TRANSFORM INFRARED - Sukma Sanjiwani Ni Made; Sudiarsa I Wayan (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
Effort defense lungs to stimuli and reflex physiological to protect the lungs from the trauma of mechanical, chemical and temperature, generally caused due to habits that are less well such as smoking, exposure to smoke cigarettes and exposure to pollution of the environment is the definition of cough (Pavort et al., 2008). Proper handling of coughs needs to be done because coughsare often a nuisance to human activities. Treatment using syrup is one of the preventivemeasures that canbe taken to treat coughin humans . The dosage form of syrup isa solution . Spectrophotometer FTIR is one ofthe instruments are much used for theanalysis of compounds of organic and has a function to determine the spectrum of vibrations of molecules and have benefits to predict the structure of the compound of thechemical.Basedon thedescription above , then do research that aims to see group functions are contained in a medicinal syrup cough OBH Combi, Viks formula 44, Syrup ifarsyl plus and woods peppermint espectorant by means of instrumentation Fourier Transform Infrared (FTIR). In this study , making a sample spectrum with DRS-8000,diffusereflectance measuring is an accessory of the IRprestige-21 instrument which is used to measure samples. The mixing of KBr powder in the sample (5-10% of the sample in KBr powder) is the first in sample analysis which is then analyzed directly by DRS. The result were obtained on cough medicine ifrasyl plus having functional groups -(CH2 )n,COC ether,C=C aromatic,C=O aldehyde,C=O asilhalida,NHsalt amine tertiary, CH alkanes andOH stretching . The functional groups found in OBHcombi cough medicine are (CH 2 ),C=C Aromatic,C=O ketone,NH tertiary amine salts,CH alkanes,NH amides andOH stretching. I medicine cough vicks formula44 hasa group function (CH 2 )n,COC ether,C=C aromatic,C=O aldehyde,NHsalt amine tertiary, CH alkanes andOH stretching . Cluster functions which are on medication cough woods namely : - (CH2 )n , COC ether, CH bending, C = O ketones, NH salt amine tertiary, CH alkanes and OH stretching .